Long Non-coding RNA N1LR Protects Against Myocardial Ischemic/Reperfusion Injury Through Regulating the TGF-β Signaling Pathway - Du, Lin; Chen, Jie; Wu, Yong; Xia, Guangwei; Chen, Mingxing; Zhao, Pei; Wang, Yao; Yao, Deshan; Liu, Fan; Zhang, Lina; Wang, Xue; Yang, Yi; et al. (Frontiers in Cardiovascular Medicine, 2021)
Long non-coding RNAs (lncRNAs) have been shown to play critical roles in various cell biological processes. However, the mechanism of lncRNAs in acute myocardial infarction (AMI) is not fully understood. Previous studies showed that lncRNA N1LR was down-regulated in ischemic cerebral stroke and its up-regulation was protective. The current study was designed to assess the protective effect of N1LR and further to explore potential mechanisms of N1LR in ischemic/reperfusion (I/R) injury after AMI. Male C57BL/6J mice and H9c2 cardiomyocytes were selected to construct in vivo and in vitro pathological models. In H9c2 cell line, N1LR expression was markedly decreased after H2O2 and CoCl2 treatments and N1LR overexpression alleviated apoptosis, inflammation reaction, and LDH release in cardiomyocytes treated with H2O2 and CoCl2. Mouse in vivo study showed that overexpression of N1LR enhanced cardiac function and suppressed inflammatory response and fibrosis. Mechanistically, we found that the expression of transforming growth factor (TGF)-β1 and smads were significantly decreased in the N1LR overexpression group exposed to H2O2. In a summary, our study indicated that N1LR can act as a protective factor against cardiac ischemic-reperfusion injury through regulating the TGF-β/Smads signaling pathway.